2014
DOI: 10.1002/14651858.cd003843.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index for improving anaesthetic delivery and postoperative recovery

Abstract: BIS-guided anaesthesia can reduce the risk of intraoperative awareness in surgical patients at high risk for awareness in comparison to using clinical signs as a guide for anaesthetic depth. BIS-guided anaesthesia and ETAG-guided anaesthesia may be equivalent in protection against intraoperative awareness but the evidence for this is inconclusive. In addition, anaesthesia guided by BIS kept within the recommended range improves anaesthetic delivery and postoperative recovery from relatively deep anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(239 citation statements)
references
References 66 publications
6
220
0
5
Order By: Relevance
“…This result is consistent with the study of Punjasawadwong et al and Recart et al, which showed that BIS monitoring was associated with shortened duration in the PACU [44,48].…”
Section: Time To Discharge From Pacu and Postoperative Symptomssupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with the study of Punjasawadwong et al and Recart et al, which showed that BIS monitoring was associated with shortened duration in the PACU [44,48].…”
Section: Time To Discharge From Pacu and Postoperative Symptomssupporting
confidence: 93%
“…We also found a statistically significant reduction in end-tidal sevoflurane concentration when using BIS monitoring as compared with routine care and anesthesia monitoring protocols. Our results are in agreement with studies by Punjasawadwong, et al who showed that BIS-guided anesthesia can significantly reduce anesthetic consumption [24] and with Croci et al who showed that BIS monitoring in women undergoing general anesthesia for gynecological laparascopic surgery reduced desflurane consumption by 34.6% [32].Our study shows that the consumption of inhaled anesthesia was significantly less in the BIS group compared to the RC group. These results confirm that using BIS monitoring reduces consumption of inhalational anesthesia.…”
Section: Inhalational Anesthetic Agent Consumptionsupporting
confidence: 93%
See 2 more Smart Citations
“…Third, there were no data pertaining to BIS values after switching off the anesthetic agents. The BIS guided extubation is found to shorten the extubation time, so may influence the results of the present study [4]. Whether there were any additional opioids given and what method was adopted to prevent intraoperative awareness, were also not addressed.…”
Section: To the Editormentioning
confidence: 87%